UPAYA POLRES DALAM MENANGGULANGI TINDAK PIDANA JUDI ONLINE DI KABUPATEN SUMENEP: (Studi Kasus, Pendidikan Pancasila dan Kewarganegaraan, STKIP PGRI Sumenep) - Wafi Barozil Abrori; Suluh Mardika Alam; Imam Syafi’i (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
Online gambling in Sumenep Regency has increased significantly due to easy digital access and low legal literacy among the community. The geographical conditions of the archipelago are also a challenge in terms of supervision and enforcement. This study aims to analyze the strategy of the Sumenep Police in dealing with online gambling crimes during the period 2022–2024. The approach used is qualitative descriptive with a case study type. Data were collected through in-depth interviews with police officers and related parties, participatory observation of educational activities and internal raids, and documentation from official sources. The results of the study show that the mitigation strategy consists of four main approaches: repressive through law enforcement against perpetrators; preventive and educational through socialization programs such as